The potential of phenothiazinium dyes as cytotoxicity markers in cisplatin-treated cells - Luiz Miguel Pereira; Gisele Bulhões Portapilla; Guilherme Thomaz Pereira Brancini; Bruna Possato; Cássia Mariana Bronzon da Costa; Péricles Gama Abreu-Filho; Mark Wainwright; Ana Patrícia Yatsuda; Gilberto Úbida Leite Braga (Scientific Reports, 2023)
Abstract Assessing the in vitro toxicity of compounds on cell cultures is an important step during the screening of candidate molecules for diverse applications. Among the strategies employed to determine cytotoxicity, MTT, neutral red, and resazurin are commonly used. Methylene blue (MB), a phenothiazinium salt, has several uses, such as dye, redox indicator, and even as treatment for human disease and health conditions, such as malaria and methemoglobinemia. However, MB has only been sparsely used as a cellular toxicity indicator. As a viability indicator, MB is mostly applied to fixed cultures at high concentrations, especially when compared to MTT or neutral red. Here we show that MB and its related compounds new methylene blue (NMB), toluidine blue O (TBO), and dimethylmethylene blue (DMMB) can be used as cytotoxicity indicators in live (non-fixed) cells treated for 72 h with DMSO and cisplatin. We compared dye uptake between phenothiazinium dyes and neutral red by analyzing supernatant and cell content via visible spectra scanning and microscopy. All dyes showed a similar ability to assess cell toxicity compared to either MTT or neutral red. Our method represents a cost-effective alternative to in vitro cytotoxicity assays using cisplatin or DMSO, indicating the potential of phenothiazinium dyes for the screening of candidate drugs and other applications.